2005
DOI: 10.1128/mcb.25.20.9054-9062.2005
|View full text |Cite
|
Sign up to set email alerts
|

Natural Meiotic Recombination Hot Spots in the Schizosaccharomyces pombe Genome Successfully Predicted from the Simple Sequence Motif M26

Abstract: The M26 hot spot of meiotic recombination in Schizosaccharomyces pombe is the eukaryotic hot spot most thoroughly investigated at the nucleotide level. The minimum sequence required for M26 activity was previously determined to be 5-ATGACGT-3. Originally identified by a mutant allele, ade6-M26, the M26 heptamer sequence occurs in the wild-type S. pombe genome approximately 300 times, but it has been unclear whether any of these are active hot spots. Recently, we showed that the M26 heptamer forms part of a lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
82
0
6

Year Published

2006
2006
2011
2011

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(89 citation statements)
references
References 41 publications
1
82
0
6
Order By: Relevance
“…Given this preference, we wondered whether ORIs and DSBs might tend to share the same IGRs. To address this issue experimentally, we tested ORI activity during the meiotic Sphase in 13 genomic loci previously found to generate DSBs (Cromie et al, 2005;Steiner and Smith 2005) (Figure 1A). Analysis of replication intermediates by two-dimensional gel electrophoresis revealed that 8 out of 13 (60%) DSB regions colocalized with active meiotic ORIs ( Figure 1B, see Figure 3B for mbs1 analysis).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given this preference, we wondered whether ORIs and DSBs might tend to share the same IGRs. To address this issue experimentally, we tested ORI activity during the meiotic Sphase in 13 genomic loci previously found to generate DSBs (Cromie et al, 2005;Steiner and Smith 2005) (Figure 1A). Analysis of replication intermediates by two-dimensional gel electrophoresis revealed that 8 out of 13 (60%) DSB regions colocalized with active meiotic ORIs ( Figure 1B, see Figure 3B for mbs1 analysis).…”
Section: Resultsmentioning
confidence: 99%
“…Further examples of DSBs regions ranging from a few hundred nucleotides up to over 2 kb have been reported by Steiner and Smith (2005) and by Cromie et al (2007). An expanded consensus of the M26 sequence has been used successfully to predict the localization of some DSBs, although not all regions harbouring the consensus generate DSBs and most genomic DSBs do not include it (Steiner and Smith, 2005;Cromie et al, 2007). A similar situation applies to other recombination hotspots associated with specific sequences such as HIS4 in S. cerevisiae (White et al, 1993;Mieczkowski et al, 2006) and a degenerate C-rich motif in humans (Myers et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, researchers have measured gene conversion tract lengths averaging less than this distance, namely several hundred base pairs (26). In prokaryotes (27, 28) and yeast (24,29), such hotspot-causing motifs have been identified. In humans, there is compelling evidence that some hotspot-causing motifs are found in retrotransposons; however, these motifs explain Ͻ20% of the inferred human hotspots (2, 30-32).…”
mentioning
confidence: 99%
“…Researchers have considered positive selection on the hotspot or multiple hotspots at different nearby positions, without successfully resolving the paradox (22,23). Another suggestion (24) is that perhaps there is some distance between the motif and the break position: after a break event, then, whether or not the motif is transmitted depends on this distance and the amount of lost DNA. In yeast, researchers have observed double-strand breaks as far as 1.3 kb away from a known motif (25).…”
mentioning
confidence: 99%